Antenatal care provider's advice is the key determinant of influenza vaccination uptake in pregnant women - Mak, D.; Regan, Annette; Joyce, S.; Gibbs, R.; Effler, P. (Wiley-Blackwell Publishing Asia, 2015)
Background: Although influenza vaccination is an important component of antenatal care and is recommended and funded by the Australian government, vaccination uptake has been low. Aims: This study compared seasonal influenza vaccination uptake among pregnant Western Australian (WA) women and identified factors associated with vaccination uptake. Materials and Methods: Adult women who were pregnant during the 2012 and 2013 influenza vaccination seasons were selected at random and invited to complete a computer-assisted telephone interview survey about whether they received influenza vaccination during pregnancy. Data analyses were weighted to the age distribution of women of reproductive age in WA. Multivariate logistic regression was used to identify factors associated with vaccination uptake. Results: Between 2012 and 2013, the proportion of WA women whose antenatal care provider recommended influenza vaccination increased from 37.6 to 62.1% and vaccination uptake increased from 23.0 to 36.5%. The antenatal care provider's advice to have influenza vaccine was the single most important factor associated with vaccination (OR 11.1, 95% CI 7.9–15.5). Most women (63.7%) were vaccinated in general practice, 18.8% in a public hospital antenatal clinic and 11.0% at their workplace. Wanting to protect their infant from infection (91.2%) and having the vaccine recommended by their GP (60.0%) or obstetrician (51.0%) were commonly reported reasons for vaccination; worrying about side effects was a common reason for nonvaccination. Conclusions: To optimise maternal and infant health outcomes, Australian antenatal care providers and services need to incorporate both the recommendation and delivery of influenza vaccination into routine antenatal care.